A Survey on Various Aggregators for Routing Delay in Wireless Sensor System - Janapriya, B; Karthikeyan, P (International Journal of Computer Sciences and Engineering, 2025)
Remote sensor systems have pulled in much research consideration lately and can be utilized in a wide range of uses. Vitality Efficiency is an essential factor for the execution of remote sensor systems (WSN). VGA can disseminate vitality scattering uniformly all through the sensors, multiplying the helpful framework lifetime for the systems. In this work, Virtual Grid Architecture (VGA) is a vitality effective directing worldview is proposed .The convention uses information total and inarrange handling to boost the system lifetime. A sensible methodology is to mastermind hubs in a changeless topology. Note that the area of the base station isn't really at the extraordinary corner of the framework; rather it tends to be situated at any subjective place. In this way VGA spares more vitality than performs better than the widely used metric as well as other two metrics devised recently in terms of energy consumption and end-to-end delay, different conventions when the transmission go is more remote.